Understanding the mechanistic basis of adaptation of perennial Sarcocornia quinqueflora species to soil salinity - Ahmed, Hassan Ahmed Ibraheem; Shabala, Lana; Shabala, Sergey (Physiologia plantarum, 2021)
Succulent halophytes can be used as convenient models for understanding the mechanistic basis of plant adaptation to salt stress. In this work, effects of salinity (0–1000 mM NaCl range) on growth, ion accumulation, and stomatal features were investigated in the succulent halophyte Sarcocornia quinqueflora. Elevated salinity levels up to 400 mM NaCl largely promoted dry matter yield, succulence, shoot surface area, and stomatal characteristics. Plant growth was optimal at 200 mM NaCl and reduced at concentrations exceeding 600 mM NaCl. Osmotic adjustment in a succulent shoot was achieved by a massive accumulation of inorganic ions, with Na+ and Cl− contributing approximately 85% of its osmolality, while organic compatible solutes and K+ were responsible for only approximately 15%. Shoot K+ was unchanged across the entire range of salinity treatments (200–1000 mM NaCl) and positively correlated with the transpiration rate (R = 0.98). Carbohydrates were not reduced at high salinity compared to plants at optimal conditions, implying that growth retardation at severe salt dosages was attributed to limitations in a vacuolar Na+ and Cl− sequestrations capacity rather than inadequate photosynthesis and/or substrate limitation. It is concluded that the superior salt tolerance of S. quinqueflora is achieved by the effective reliance on Na+ and Cl− accumulation for osmoregulation and turgor maintenance, and efficient K+ homeostasis for adequate stomatal functioning over the entire salinity range. The above findings could be instrumental in developing strategies to improve salinity stress tolerance in perennial horticultural crops and optimize their water‐use efficiency.